Sunan Ampel Dan Pendidikan Islam: Peran, Metode, Dan Pengaruhnya Dalam Perkembangan Keislaman Di Nusantara - Novi Fitriani Rosyidah; Ayu Pratama Ameliah; Masrurotun Khoiriyah; Moh. Kusno (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
This study aims to examine the role, method, and influence of Sunan Ampel in the development of Islamic education in Nusantara. Sunan Ampel is one of the important figures in the history of Islam in Nusantara, especially in the development of Islamic education. Using historical research methods and content analysis, this study finds that Sunan Ampel plays a significant role in developing Islamic education in Nusantara through innovative and effective teaching methods. This study also finds that Sunan Ampel has a significant role in developing an Islamic education system based on Islamic values and local culture. He successfully developed an Islamic education curriculum that includes fields such as Al-Qur'an, Hadits, Fiqh, and others. The influence of Sunan Ampel on the development of Islamic education in Nusantara is also significant. He successfully inspired subsequent generations to develop Islamic education in Nusantara. This study is expected to contribute to the development of Islamic education in Indonesia and enrich understanding of the history and development of Islam in Nusantara.